2012
DOI: 10.1128/iai.05695-11
|View full text |Cite
|
Sign up to set email alerts
|

Role of Toll Interleukin-1 Receptor (IL-1R) 8, a Negative Regulator of IL-1R/Toll-Like Receptor Signaling, in Resistance to Acute Pseudomonas aeruginosa Lung Infection

Abstract: Toll interleukin-1 receptor (IL-1R) 8 (TIR8), also known as single Ig IL-1 receptor (IL-R)-related molecule, or SIGIRR, is a member of the IL-1R-like family, primarily expressed by epithelial cells. Current evidence suggests that TIR8 plays a nonredundant role as a negative regulator in vivo under different inflammatory conditions that are dependent on IL-R and Toll-like receptor (TLR) activation. In the present study, we examined the role of TIR8 in innate resistance to acute lung infections caused by Pseudom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 59 publications
(70 reference statements)
5
51
3
1
Order By: Relevance
“…A possible reason for these opposite function of BMP4 in regulating immune responses under different conditions may be due to the cross-talk between BMP family members and other signaling pathways [15], among them the TLR signaling that mediates innate or adaptive immune responses might be a top candidate [16][17][18][19][20]. The different pathophysiological environment might also contribute to the differential effects of BMP4 in cells from different location.…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason for these opposite function of BMP4 in regulating immune responses under different conditions may be due to the cross-talk between BMP family members and other signaling pathways [15], among them the TLR signaling that mediates innate or adaptive immune responses might be a top candidate [16][17][18][19][20]. The different pathophysiological environment might also contribute to the differential effects of BMP4 in cells from different location.…”
Section: Discussionmentioning
confidence: 99%
“…In a murine model of pulmonary tuberculosis and acute Pseudomonas aeruginosa lung infection, TIR8 Ϫ/Ϫ mice were shown to have increased mortality (13,37). Huang et al (16) reported that mice treated with anti-TIR8 Ab had increased stromal damage and bacterial load in the cornea in a model of Pseudomonas aeruginosa keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…After priming by LPS or other PAMPs, activation of the NLR family CARD domain-containing protein 4 (NLRC4) inflammasome by internalized flagellin stimulates caspase-1, resulting in pyroptosis -a highly proinflammatory mode of cell death associated with tissue damage -and release of inflammatory cytokines, such as IL-1β and IL-18 (14)(15)(16)(17)(18)(19)(20)(21)(22). Both IL-1β and IL-18 have been identified as mediators of local inflammation in the lung and tissue remodeling systemically (1, 2, [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%